Peningkatan Literasi Digital Masyarakat Desa melalui Pelatihan Internet Sehat dan Aman - Susan Dian Purnamasari; Fatmasari Fatmasari; Afny Istiqomah (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2026)
The rapid advancement of information and communication technology has significantly expanded internet accessibility, including in rural communities. However, increased internet access has not been accompanied by adequate digital literacy, leaving many community members vulnerable to various digital risks such as misinformation, online fraud, personal data breaches, and unethical online behavior. This community engagement program aimed to enhance the digital literacy of residents in Purwosari Village, Tanjung Lago District, Banyuasin Regency through a healthy and safe internet training program. The program was implemented using a participatory approach consisting of preliminary coordination with village authorities, community needs assessment, preparation of educational materials, interactive training sessions, hands-on assistance, and evaluation through discussions and quizzes. Approximately 30 participants, including housewives, adolescents, and community leaders, attended the training. The educational materials covered fundamental concepts of digital literacy, digital ethics, online privacy and personal data protection, identification of misinformation and online scams, and the productive use of digital technology to support education, economic activities, and social interaction. The program outcomes indicated an improvement in participants' understanding of responsible internet use, as reflected in their increased ability to identify reliable information, recognize the importance of protecting personal data, and apply safer and more ethical digital practices in their daily lives. This community engagement initiative is expected to serve as an initial step toward strengthening digital literacy in rural communities and fostering a digitally competent society capable of utilizing information technology safely, responsibly, and productively.